Pengaruh Kinerja Lingkungan, Ukuran Perusahaan, Profitabilitas dan Pengungkapan Emisi Karbon - Eka Dewayani, Ni Putu; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi, 2021)
This study aims to examine empirically the influence of environmental performance, size, and profitability on carbon emission disclosure at non-financial companies listed on Indonesia Stock Exchange. Population used in this study in non-financial companies listed on Indonesia Stock Exchange on 2017 and 2018. The technique of determining sample using purposive sampling and obtained 112 observation companies. The research data analysis used linear regression analysis. Based on the results of the analysis found that size has a significant positive effect on carbon emission disclosure. This shows that if the size of the company increase, the amount of carbon emission disclosure increases. Environmental performance and profitability has no effect on carbon emission disclosure. Keywords: Carbon Emission Disclosure; Enviromental Performance; Size; Profitability.